GROWTH AND YIELD RESPONSE OF SHALLOT PLANTS TO THE ADMINISTERING OF RICE HUSK BIOCHAR AND MANURE: RESPON PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH TERHADAP PEMBERIAN BIOCHAR SEKAM PADI DAN PUPUK KANDANG - Tasliati Djafar; Wilis, Ruhalena; Nurlia Farida; Elviani (PT. ROCE WISDOM ACEH, 2025)
This research examines the effect of rice husk biochar and manure on the growth of shallots and the interaction between the two treatments carried out. This research was conducted in Gampong Pineung, Syiah Kuala District, Banda Aceh, from September to December 2023. The method used was a Randomized Block Design (RBD) with a 3x3 factorial design and three replications. The factors tested in this research were the dose of rice husk biochar (0, 10, and 20 tons/ha) and the dose of manure (0, 10, and 20 tons/ha). Several parameters were observed, such as plant height at the age of 15, 30, and 45 dap, the number of tubers per clump at the age of 30 and 45 dap, the weight of wet tubers and dry tubers per clump, and the potential yield per hectare. The results of the research showed that the dose of biochar had a very significant impact on plant height at 30 and 45 dap, the weight of wet tubers, the weight of dry tubers, and the potential yield per hectare. Plant height at 15, 30, and 45 dap, number of tubers per hill at 30 and 45 dap, wet and dry tuber weight per hill, and potential yield per hectare. The study showed that plant height at 30 and 45, wet tuber weight, dry tuber weight, and potential yield per hectare were all significantly affected by biochar dosage. It had no visible impact on the number of tubers per hill at 30 and 45 dap, or on plant height at 15. Plant height at 15 and 30 days was significantly affected by manure application, but plant height at 45 dap, number of tubers per hill at 30 and 45 dap, wet and dry tuber weight, and potential yield per hectare were not affected. In the study of shallot growth and yield results, there was no clear interaction between manure dosage and rice husk biochar